ISUPPORT OF INNOVATIVENESS IN POLISH AGRICULTURE - Bożena Nosecka (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2018)
Innovativeness is the cross-cutting goal of the 2020 Strategy implemented in the EU. Innovativesolutions and broadly based development on the achievements of knowledge lead to the improvement of thecompetitiveness of the EU economy and its various departments in comparison to other world economies.In order to introduce innovativeness and achievements of knowledge in the agriculture of EU countries,the increase in share of payments related to the second pillar of the CAP, including structural support infunds allocated for the implementation of the common agricultural policy is required. The article presentsan analysis of the titles of innovation support in Poland (actions, sub-measures, operations) from thesecond pillar of the CAP implemented from the resources of the Rural Development Program (RDP). Thescope of funding from RDP funds in 2014-2020 of activities and operations directly and indirectly relatedto the introduction and dissemination of innovative solutions in Polish agriculture was also assessed.